Sex Differences and Violence Among Primary School Students - Marković, Živorad M.; Trifunović, Vesna S. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This is the micro research which studied the connection between gender and violence in older primary school students with the goal of discovering exposure of gender members to violence in school context and the ways of reacting to the violence. The researchers from different scientific disciplines have been permanently involved in studying the problem of violence for more than a decade with the goal to lessen the high percentage of violence in schools. In this sense, this research, with its range and character, represents the contribution in discovering characteristics of violence in schools in one specific local area, which could fill in the wholeness of this phenomenon. The research involved students of the final grade of primary school on the territory of the municipality of Svilajnac (which is in central part of Serbia) and it was performed in December 2015. 236 students were surveyed. The survey consisted of the following categories a) the social matrix of families in which the students live b) the presence and frequency of different types of violence between students in primary schools c) the attitudes of students of both genders about the violence, exposure to violence in school and the ways of reacting to violence. In the frame of quantitative analysis of the data the following was applied: percentual research of frequencies and Pierson’s hi-square test (χ2) for testing of hyphothesis about the significance of differences. The main results of the research showed: a)      There is no statistically significant difference in exposure to violence in school between male and female students of primary school age; both genders are exposed to verbal and physical violence; male students (45.7%) are more exposed to physical, while female students (38.3%) are more exposed to verbal violence. b)      There is no statistically significant difference in the readiness of students considering their gender to help another student who is victimised in school: 48.1% of male students and 34.6% of female students claim that they would be ready to help students who are suffering violence in a school context without demanding support from other students. c)      The students of both genders are more ready to help the victims of the violence in school than the victims of the violence outside school: the readiness of helping unknown person who is exposed to violence outside school is in percents 34.1% of male students and 28% of female students. d)      There are no statistically significant differences between male and female students in the ways of reacting to the violence, although a somewhat larger percent of male students (47.3%) than female students (31.8%) would react the same to the violence. However, there is also a deviation from stereotypes that girls are more inclined to suffer violence than boys since in the researched population there is a datum which shows that a larger percent of male students (14.0%) responds to the violence by being silent and suffering than female students where only 9.3% decide to react in such a way. The results of the research showed that the basic hypothesis — gender of primary school students determines significantly their exposure to different types of school violence and the ways of reacting to violence — was not confirmed. The results showed that there is no statistically significant difference between male and female students in their exposure to violence, reaction to violence and their readiness to help the victim of the violence. (1)   Special hypothesis — the most frequent form of violence between students in primary schools is verbal, and the least present is physical— is partly confirmed. It was shown that the most frequent ways of violence between male students in older primary school grades are physical violence, verbal violence, and hooliganism and bullying. (2)   Special hypothesis — significantly small number of primary school male students was exposed to violence, and those between them who suffered violence were mostly exposed to physical violence — was not confirmed. Male students were somewhat less exposed to physical violence (17.1%) the female students where 20,6% of them suffered physical violence more times during the last school year. (3)   Special hypothesis — significantly small percentage of primary school female students was exposed to violence, and those between them who suffered violence were mostly exposed to verbal violence — was partly confirmed. (4)   Special hypothesis — the most frequent reaction of male students who were exposed to violence in school is to respond in the same way, by violence — was confirmed: 47,3% of male students and 31.8% of female students react exactly in this way while exposed to violence. (5)   Special hypothesis — the most frequent reaction of female students who are exposed to violence in school is to be silent and suffer — was not confirmed. The data showed that female students are not inclined to this reaction like male students. (6)   Special hypothesis — male students in primary schools show significantly more readiness to help the victim of violence than female students — was not confirmed. The data showed that there is no statistically significant difference between readiness of male and female students to help the victim of the violence. The problem of violence in school is a popular topic and it opens a lot of controversies: on one side, school laws aspire to norm every segment of school life because of which students are in “danger” to be labeled as dangerous; on the other side, school evidence shows high percentage of exposure of students to violence and its high frequency. Because of that, the problem of school violence cannot be resolved only by laws and proposed activities which are controlled by school bodies, but on the level of the whole society, connected actions in all its structures — macro, meso and micro structures. With the special accent on developing of educational role of schools and promoting of healthy lifestyles.
Keywords: sex differences; school violence; adolescence; primary school students; school